ALCOHOL-BASED HAND SANITIZER: ABUSE DURING LOCKDOWN AMIDST COVID-19 PANDEMIC - SARMA, BEDANTA; KUMARAN M, SENTHIL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Alcohol-based hand sanitizers are popular alternative to the traditional handwashing with soap and water in both healthcare and community settings. Although some people use to carry small sanitizer bottles with them during travel; its utilization by common people come into picture during the COVID-19 pandemic. Because of sudden requirement of those products within a short time, there was even shortage during the initial days. Once nationwide lockdown was declared in India, to prevent community spread; all the shops were closed including wine shops. During this tough time, many alcohol withdrawal cases were reported from different regions. Some people started taking hand sanitizers as a replacement for potable alcohol. Because of high alcoholic content and adulteration with methanol or any other substances, most of the people became ill and they were hospitalized. Deaths were also reported from different states following its consumption. Addiction to hand sanitizers is now considered as one of the overlooked problems globally. It is very difficult to erase the problem, especially among teenagers. Multi-task approach involving different populations at different levels are required to handle this problem.